Application of a Hopfield type neural network to the analysis of elastic problems with unilateral constraints - Waszczyszyn, Zenon; Pabisek, Ewa (Computer Assisted Methods in Engineering and Science, 2023)
On the base of Hopfield- Tank neural network the Panagiotopoulos approach is briefly discussed. The approach is associated with the analysis of quadratic programming problem with unilateral constraints. Then modifications of this approach are proposed. The original Panagiotopoulos approach is illustrated by the analysis of crack detachment in an elastic body [11]. Efficiency of the proposed modifications is shown on a numerical example of an angular plate. Finally some special conclusions are expressed.